Pengaruh Penggunaan Media Audiovisual Terhadap Motivasi Belajar Siswa dalam Pembelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP Negeri 2 Balige Tahun Pelajaran 2024/2025 - Handoko Pardosi; Taripar Aripin Samosir; Boho Parulian Pardede (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
The use of audiovisual media is one of the successes of learning, including student learning motivation. This study aims to determine the positive and significant effect of the Use of Audiovisual Media on the Learning Motivation of Class VIII Students of SMP Negeri 2 Balige in the 2024/2025 Academic Year. Quantitative method, the Research Population was all class VIII students of SMP Negeri 2 Balige totaling 216 people and the sample was taken 15% of the total population of 216 people so that the sample of this study was 32 people. Using regression analysis techniques. Proven through the following data analysis: 1) Influence test: Regression equation test Ŷ = 0.292 + 33.506X. b) The significant influence test obtained the value of tcount> ttable = 1.8019> 2.024, then Ha is accepted Ho is rejected. Based on the results of the study, it is known that the use of audiovisual media on student learning motivation can increase. This can be seen from the average value of 3. Thus, the researcher concluded that there is learning motivation for Christian Religious Education students in the 2024/2025 Academic Year.